Different Dimensions of Screenwriting in Dr Shahida Sardar’s Poetry: ڈاکٹرشاہدہ سردا ر کی شاعری میں منظر نگاری کی مختلف جہتیں (DARYAFT, 2022)
Dr Shahida Sardar is a renowned poetess of Khyber Pakhtunkhwa. Her poetic excellence encompasses both Urdu as well as Pashto. The soul of her poetry unlike others isn’t only limited to romance and fairytales but it is a reflection of the surroundings around her. Her poetry presents such clear picture of modern Khyber Pakhtunkhwa that a new reader without knowing her personally, can easily determine her birth place through her poetry which is quite extraordinary
Keywords: Dr. Sahida Sardar, Poetess, KPK, Urdu, Pashto, Romance, Fairytales, Modern, Extraordinary